ANALISIS PENGARUH STRUKTUR MODAL TERHADAP ECONOMIC VALUE ADDED (EVA) (Students' Journal of Accounting and Banking, 2013)
The aim of this research is to examine the effect of capital structure to Economic Value Added. According to traditional approach theory, the change of the optimal capital structure and increase firm value by the financial leverage. The financial leverage in this research are Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Long Term Debt to Equity Ratio (LDER), Long Term Debt to Asset Ratio (LDAR), and Equity to Asset Ratio (EAR). Researcher use purposive sampling, this study get the 75 firms’s sample and then data have test use normality and classic assumption test. To test hypothesis, researcher use multiple regression model. The result of partial’s test show that Debt to Equity Ratio, Long Term Debt to Equity Ratio, and Equity to Asset Ratio have negative dan significant influence to Economic Value Added. Debt to Asset Ratio has positive and significant influence and Long Term Debt to Asset Ratio has positive and insignificant influence to Economic Value Added. Keywords: Debt to Equity Ratio, Debt to Asset Ratio, Long Term Debt to Equity Ratio, Long Term Debt to Asset Ratio, Equity to Asset Ratio, and Economic Value Added.